Body Condition and Productivity, Health and Welfare - García, María-Luz; Argente, María-José (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on applied research on growth traits, fat reserves, fatty acid profiles and enriched diets and their effects on reproduction, health status and welfare. The studies contained in the volume have been carried out in both monogastric organisms and ruminants, fish, broilers or pigeons. Fundamental studies with rats or mice are also presented. The reader will find novel research about the effects of the degree of fatness and muscularity determined by ultrasound method on sows´ reproductive performance, genetic studies on fatty acid profiles and growth traits in rabbits and Gilthead Seabream; nutritional studies addressing diets enriched with bee pollen in rats, postbiotics in male rabbits, concentrate and bypass supplementations in buffaloes; and interesting studies on the welfare assessment of meat sheep, rabbits, racing pigeons, broilers, alpacas and llamas using body condition measurements.